Recent progress in performance optimization of Cu-SSZ-13 catalyst for selective catalytic reduction of NOx - Li, Pan; Xin, Ying; Zhang, Hanxue; Yang, Fuzhen; Tang, Ahui; Han, Dongxu; Jia, Junxiu; Wang, Jin; Li, Zhenguo; Zhang, Zhaoliang (Frontiers in Chemistry, 2022)
Nitrogen oxides (NOx), which are the major gaseous pollutants emitted by mobile sources, especially diesel engines, contribute to many environmental issues and harm human health. Selective catalytic reduction of NOx with NH3 (NH3-SCR) is proved to be one of the most efficient techniques for reducing NOx emission. Recently, Cu-SSZ-13 catalyst has been recognized as a promising candidate for NH3-SCR catalyst for reducing diesel engine NOx emissions due to its wide active temperature window and excellent hydrothermal stability. Despite being commercialized as an advanced SCR catalyst, Cu-SSZ-13 catalyst still confronts the challenges of low-temperature activity and hydrothermal aging to meet the increasing demands on catalytic performance and lifetime. Therefore, numerous studies have been dedicated to the improvement of NH3-SCR performance for Cu-SSZ-13 catalyst. In this review, the recent progress in NH3-SCR performance optimization of Cu-SSZ-13 catalysts is summarized following three aspects: (1) modifying the Cu active sites; (2) introducing the heteroatoms or metal oxides; (3) regulating the morphology. Meanwhile, future perspectives and opportunities of Cu-SSZ-13 catalysts in reducing diesel engine NOx emissions are discussed.